Mortality from esophagectomy for esophageal cancer across low, middle, and high-income countries: An international cohort study. Issue 6 (June 2021) - ,; Kamarajah, S.K.; Nepogodiev, D.; Bekele, A.; Cecconello, I.; Evans, R.P.T.; Guner, A.; Gossage, J.A.; Harustiak, T.; Hodson, J.; Isik, A.; Kidane, B.; et al.
Abstract: Background: No evidence currently exists characterising global outcomes following major cancer surgery, including esophageal cancer. Therefore, this study aimed to characterise impact of high income countries (HIC) versus low and middle income countries (LMIC) on the outcomes following esophagectomy for esophageal cancer. Method: This international multi-center prospective study across 137 hospitals in 41 countries included patients who underwent an esophagectomy for esophageal cancer, with 90-day follow-up. The main explanatory variable was country income, defined according to the World Bank Data classification. The primary outcome was 90-day postoperative mortality, and secondary outcomes were composite leaks (anastomotic leak or conduit necrosis) and major complications (Clavien-Dindo Grade III - V). Multivariable generalized estimating equation models were used to produce adjusted odds ratios (ORs) and 95% confidence intervals (CI95% ). Results: Between April 2018 to December 2018, 2247 patients were included. Patients from HIC were more significantly older, with higher ASA grade, and more advanced tumors. Patients from LMIC had almost three-fold increase in 90-day mortality, compared to HIC (9.4% vs 3.7%, p < 0.001). On adjusted analysis, LMIC were independently associated with higher 90-day mortality (OR: 2.31, CI95% : 1.17–4.55, p = 0.015). However, LMIC were not independently associated with higher rates of anastomotic leaks (OR: 1.06, CI95% : 0.57–1.99, p = 0.9) or major complications (OR: 0.85, CI95% : 0.54–1.32, p = 0.5), compared to HIC. Conclusion: Resections in LMIC were independently associated with higher 90-day postoperative mortality, likely reflecting a failure to rescue of these patients following esophagectomy, despite similar composite anastomotic leaks and major complication rates to HIC. These findings warrant further research, to identify potential issues and solutions to improve global outcomes following esophagectomy for cancer.